“Education will get you to the station”: MARGINALIZED STUDENTS’ EXPERIENCES AND PERCEPTIONS OF MERIT IN ACCESSING UNIVERSITY - James, Carl; Taylor, Leanne (Canadian Journal of Education/Revue canadienne de l’éducation, 2008)
This article explores how four minority students in a university access program reconciled their presence on merit. They shared their experiences over two years through their application statements, life history interviews, weekly group sessions, and personal journal entries. Consistent with the discourse of merit, participants believed that by exercising agency and taking responsibility for their schooling, education will work to their benefit. They reconceptualized the access program as a scholarship program and affirmed pride in being university students, with a sense of obligation to their immigrant parents and a desire to give back to their communities. Key words: immigrant youth, access programs, racism, parental expectations Les auteurs analysent comment quatre étudiants faisant partie de groupes minoritaires et participant à un programme d’accès à l’université réconcilient leur présence au mérite. Ces étudiants partagent leurs expériences par divers moyens : textes rédigés lors de leurs demandes d’admission, entrevues portant sur leur histoire de vie, sessions hebdomadaires en groupe et journaux intimes. Dans le droit fil du discours sur le mérite, les participants croient que s’ils prennent leur éducation en main, elle leur sera profitable. Ils reconceptualisent le programme d’accès comme un programme de bourse; se disant fiers d’aller à l’université, ils se sentent redevables à l’égard de leurs parents immigrants et souhaitent faire profiter leurs communautés de leur acquis. Mots clés: jeunes immigrants, programmes d’accès, racisme, attentes des parents